Documented 2009 H1N1 influenza A infection in pediatric liver transplant patients – Description and follow-up of 7 patients - Mustafa Serdar CANTEZ; Nelgin GERENLİ; Selda HANÇERLİ TÖRÜN; Nuran SALMAN; Özlem DURMAZ (Turkish Journal of Gastroenterology, 2019)
-